Co-Occurring Potentially Actionable Oncogenic Drivers in Non-Small Cell Lung Cancer - Zhao, Yiming; Wang, Shuyuan; Yang, Zhengyu; Dong, Yu; Wang, Yanan; Zhang, Lele; Hu, Hai; Han, Baohui (Frontiers in Oncology, 2021)
Background Several oncogenic drivers in non-small cell lung cancer (NSCLC) are considered actionable with available or promising targeted therapies. Although targetable drivers rarely overlap with each other, there were a minority of patients harboring co-occurring actionable oncogenic targets, whose clinical characteristics and prognosis are not yet clear. Methods A total of 3,077 patients with NSCLC who underwent molecular analysis by NGS were included, and their demographic and clinical data were retrospectively collected. Results Our study found that the frequency of NSCLC patients harboring co-occurring potentially actionable alterations was approximately 1.5% (46/3077); after excluding patients with EGFR-undetermined mutations, the incidence was 1.3% (40/3077); 80% (37/46) harbored both EGFR mutations and other potentially actionable drivers such as MET amplification (21.6%; 8/37) and alterations in ERBB2 including mutations (27%; 10/37) and amplification (21.6%; 8/37); other combinations of potentially actionable drivers including alterations in ERBB2, KRAS, MET, ALK, and RET were also identified. Additionally, de novo MET/ERBB2 amplification in patients harboring EGFR-mutant NSCLC treated with first-generation EGFR tyrosine kinase inhibitors (TKIs) was associated with shorter PFS (p < 0.05). The efficacy of TKIs in NSCLC patients harboring other co-occurring potentially actionable drivers varied across different molecular subtypes. Conclusions Approximately 1.5% of NSCLCs harbored co-occurring potentially actionable oncogenic drivers, commonly involving EGFR mutations. Co-occurring actionable targets may impact the efficacy of TKIs; therefore, future clinical trials in these patients should be anticipated to tailor the combination or sequential treatment strategies.